1998
DOI: 10.1094/pdis.1998.82.9.1048
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Racial Composition ofPhytophthora sojaein Australia Between 1979 and 1996

Abstract: Surveys of commercial soybean fields, disease nurseries, and trial plots of soybean were conducted throughout eastern Australia between 1979 and 1996, and 694 isolates of Phytophthora sojae were collected and classified into races. Fourteen races, 1, 2, 4, 10, 15, and 25, and eight new races, 46 to 53, were identified, but only races 1, 4, 15, 25, 46, and 53 were found in commercial fields. Races 1 and 15 were the only races found in commercial fields in the soybean-growing areas of Australia up until 1989, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 33 publications
0
42
0
2
Order By: Relevance
“…What types of PRR resistance were present in the cultivars used since 2006 is difficult to identify. In the USA and Australia, the increased selection pressure exerted by Rps genes included in commercial soybean cultivars may have driven the development of a diverse P. sojae population with greater genetic variability, and the production of more pathotypes Ryley et al 1998;Jackson et al 2004). In Ohio, after a systematic soil survey, it was observed that between 51 and 96 % of the locations had at least one isolate with virulence to commonly deployed Rps genes 1a, 1b, 1c, 1k, 3a, and 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What types of PRR resistance were present in the cultivars used since 2006 is difficult to identify. In the USA and Australia, the increased selection pressure exerted by Rps genes included in commercial soybean cultivars may have driven the development of a diverse P. sojae population with greater genetic variability, and the production of more pathotypes Ryley et al 1998;Jackson et al 2004). In Ohio, after a systematic soil survey, it was observed that between 51 and 96 % of the locations had at least one isolate with virulence to commonly deployed Rps genes 1a, 1b, 1c, 1k, 3a, and 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous surveys for pathotype composition of P. sojae populations have been carried out primarily in the USA Yang et al 1996;Leitz et al 2000;Kaitani et al 2001;Dorrance et al 2003;Jackson et al 2004;Malvick and Grunden 2004;Nelson et al 2008), as well as in Argentina (Barreto et al 1995;Gally et al 2007), and Australia (Ryley et al 1998). Only the differential with Rps7 had a susceptible reaction (Costamilan et al 2010) to one isolate from Passo Fundo, RS, in the first study about pathogenicity of P. sojae in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that several races can exist randomly in one region, even in the presence of a predominant race. This tendency also can be seen in Ohio (Schmitthenner et al 1994), Indiana (Laviolette and Athow 1981), Iowa (Yang et al 1996), and Australia (Ryley et al 1998). As a consequence, several new resistant cultivars must be bred to the dominant races in each region.…”
Section: Interaction Between Several Rps Genes and Races In Hyogomentioning
confidence: 90%
“…Shifts in the frequency of prevalent races were not seen during the 3-year survey (Table 3). In worldwide research, temporal changes in the racial composition of P. sojae were caused by the resistance genes used in commercial cultivars, that is, by shifts in the compatible and incompatible genotypes in cultivars (Anderson and Bussell 1992;Ryley et al 1998). Such changes in racial dynamics did not occur in Hyogo from 2002 to 2004 because few soybean cultivars were grown in the regions surveyed.…”
Section: Interaction Between Several Rps Genes and Races In Hyogomentioning
confidence: 99%
“…), caused by Phytophthora sojae was Wrst noted as a soil-borne disease of unknown etiology in Northeast Indiana, USA in 1948(Schmitthenner 1989. This disease was especially severe in low, poorly drained and clay soil, and has been found in most soybean-growing regions (Bernard et al 1957;Kaufmann and Gerdemann 1958;Hildebrand 1959;Ryley et al 1998;Jee et al 1998 andSu andYao 1993). During wet springs about 25% of damping-oV of soybeans in Iowa is caused by PRR (Rizvi and Yang 1996).…”
Section: Introductionmentioning
confidence: 95%